2016
DOI: 10.1177/1475725716671824
|View full text |Cite
|
Sign up to set email alerts
|

The Socratic Method: Empirical Assessment of a Psychology Capstone Course

Abstract: Although students make some epistemological progress during college, most graduate without developing meaning-making strategies that reflect an understanding that knowledge is socially constructed (Pizzolato, 2006). Using a pretest-posttest design and a withinsubjects 2 x 2 mixed-design ANOVA, this study reports on empirical findings supportive of the Socratic method of teaching as effective in challenging and changing psychology capstone students' levels of epistemological maturity as measured by the Learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Perry’s (1970) full learning model is based on a stage model of intellectual development and encompasses nine stages or positions. Starting with basic duality (in which knowledge is basically right or wrong), it culminates with a sense of personal identity and commitment despite uncertainty or conflicting sources (Burns, Stephenson, & Bellamy, 2016; Thomas, 2008). A precise balance of academic challenge and support (such as that found in the accelerator model) can aid a student’s movement through each of these stages (Brand, 1988; Canon & Newble, 2000; De L’Etoile, 2008; Nilson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Perry’s (1970) full learning model is based on a stage model of intellectual development and encompasses nine stages or positions. Starting with basic duality (in which knowledge is basically right or wrong), it culminates with a sense of personal identity and commitment despite uncertainty or conflicting sources (Burns, Stephenson, & Bellamy, 2016; Thomas, 2008). A precise balance of academic challenge and support (such as that found in the accelerator model) can aid a student’s movement through each of these stages (Brand, 1988; Canon & Newble, 2000; De L’Etoile, 2008; Nilson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The Socratic method can also encourage collaboration through establishing an expressive and supportive environment where constructive student group discussion is promoted (Burns, Stephenson, & Bellamy, 2016;Kerr, 1999). This can be achieved by the facilitator modeling positive group dynamics, offering a speculative "nudge" in discourse when it is necessary, and sitting back and allowing student discourse when possible and appropriate (Jones, 2014).…”
Section: Socrates and The Art Of Skillful Questioningmentioning
confidence: 99%
“…Valid assessment requires careful consideration of the whole: purpose, scope, and method. For example, Burns, Stephenson and Bellamy (2016) used the Learning Environment Preference instrument (LEP) (Moore, 1989) to assess 135 students' epistemological development in a series of separate 15-week capstone courses. Through the LEP measurements the study found that a capstone course, based on the Socratic teaching method, enabled students to demonstrate the ability to tolerate ambiguity and to challenge preconceived beliefs through the use of open discussion and scaffolded-learning, in contrast with the lecture-only control group.…”
Section: How To Assess Integrative Learningmentioning
confidence: 99%
“…The stages of simple to complex questions become the plot in this Socratic method, which is used to test the validity of students' beliefs about a problem object. The Socratic method is a very constructive method or builds knowledge for students (Stoddard & O'Dell, 2016;Burns et al, 2016;Astuti S. et al, 2019;Ismah & Muthmainnah, 2021;.…”
Section: ▪ Introductionmentioning
confidence: 99%